Shariah Compliance Akad Rahn Lembaga Keuangan Mikro Syariah (Studi Kasus BMT Mitra Muamalah Jepara) - Edi Susilo (IQTISHADIA Jurnal Ekonomi & Perbankan Syariah, 2017)
Rahn Contract (Gold Pawn) has a high level of security and low risk, because the guarantee is to save (Rahn) members liquid assets. When members are in default (wanprestasi), it can be executed on collateral. This study uses qualitative descriptive analytic. The results showed Rahn Contract has good prospects, in compliance with the fatawa of National Sharia Board - Indonesian Council of Ulama (DSN – MUI) about Rahn, but is weak in supervision of the Sharia Supervisory Board (DPS) and constrained by human resources, competition, insurance and promotion.